2018
DOI: 10.1186/s13006-018-0193-6
|View full text |Cite
|
Sign up to set email alerts
|

Prelacteal feeding and associated factors in Ethiopia: systematic review and meta-analysis

Abstract: BackgroundPrelacteal feeding can be defined as giving any solid or liquid foods other than breast milk during the first three days after birth. It affects timely initiation of breastfeeding and exclusive breastfeeding practices. Even though the issue was investigated in Ethiopia, fragmented and inconsistent findings were reported. Therefore, the main objective of this meta-analysis was to estimate the pooled prevalence of prelacteal feeding and associated factors in Ethiopia.MethodsThe preferred reporting item… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
50
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 47 publications
7
50
1
Order By: Relevance
“…Despite the recommendations by infant and young child feeding, Government of India and the WHO, delayed initiation of breast feeding was quite high in the study which is comparable to studies in LMICs. [11][12][13][14] The reason for which was found to be that the colostrum was thought to be unworthy of giving to the baby Figure 5. According to a study conducted in western Nepal, a significant number of mothers gave colostrum as the first meal to 86.2% babies, while the remaining 14% babies were given a fluid other than breast milk as their first feed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the recommendations by infant and young child feeding, Government of India and the WHO, delayed initiation of breast feeding was quite high in the study which is comparable to studies in LMICs. [11][12][13][14] The reason for which was found to be that the colostrum was thought to be unworthy of giving to the baby Figure 5. According to a study conducted in western Nepal, a significant number of mothers gave colostrum as the first meal to 86.2% babies, while the remaining 14% babies were given a fluid other than breast milk as their first feed.…”
Section: Discussionmentioning
confidence: 99%
“…15 Various family rituals and myths were found to be responsible as in our study. [11][12][13][14] Another reason for the delay was found to be unpopularity of the early skin to skin contact of mother with newborn as recommended by WHO due to separation of the mother-baby pair for routine post-delivery procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ethiopia breastfeeding is almost universal across a country, however, it does not always meet WHO/UNICEF recommendations [24]. Studies revealed that more than 25% of the mothers were giving prelacteal feeding instead of colostrum to their newborn [25]. Nearly 40% of the mothers did not initiate colostrum within one hour of birth and only 60% of mothers practiced exclusive breastfeeding in the rst 6 months of life [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Socio-demographic related predictors of infant feeding practices are relatively well researched. The literature consistently show that maternal age, socio-economic status, level of education, marital status and location are associated with infant feeding practices [18][19][20][21][22][23][24]. However, researches examining psychosocial predictors of IFPs are very limited.…”
mentioning
confidence: 99%